2007
DOI: 10.1002/bit.21510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEG modification on subtilisin Carlsberg activity, enantioselectivity, and structural dynamics in 1,4‐dioxane

Abstract: The employment of enzymes as catalysts within organic media has traditionally been hampered by the reduced enzymatic activities when compared to catalysis in aqueous solution. Although several complementary hypotheses have provided mechanistic insights into the causes of diminished activity, further development of biocatalysts would greatly benefit from effective chemical strategies (e.g., PEGylation) to ameliorate this event. Herein we explore the effects of altering the solvent composition from aqueous buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…One strategy for broadening the range of activities over which enzyme catalysis and protein dynamics can be studied concurrently is to employ nonaqueous or organic solvents. For example, a correlation between molecular dynamics, as evidenced by a reduced rate of amide H/D exchange, and biocatalyst activity has been observed for PEGylated subtilisin Carlsberg (SC) in 1,4-dioxane (9).…”
mentioning
confidence: 99%
“…One strategy for broadening the range of activities over which enzyme catalysis and protein dynamics can be studied concurrently is to employ nonaqueous or organic solvents. For example, a correlation between molecular dynamics, as evidenced by a reduced rate of amide H/D exchange, and biocatalyst activity has been observed for PEGylated subtilisin Carlsberg (SC) in 1,4-dioxane (9).…”
mentioning
confidence: 99%
“…Chiu et al reported that pegylation activates and stabilizes trypsin, although the mechanisms are not known. 39) In non-aqueous solution, pegylation increases the activities of various enzymes such as lipase 40) and subtilisin Carlsberg, 41) but in aqueous solution, it decreases the activities of various enzymes such as -chymotrypsin 42) and lysozyme. 43) In the case of -chymotrypsin, pegylation decreased the k cat values without changing the K m values.…”
Section: Discussionmentioning
confidence: 99%
“…S2). Lysozyme has seven NH2 residues from lysozyme available for modification [30]. Thus, two (6 × 35%≈2.1) amine groups on enzyme molecule were modified.…”
Section: Enzyme Modificationmentioning
confidence: 99%